The Effect of the Jigsaw Cooperative Learning Model Assisted by Puzzle Media on Improving Learning Concentration in Children with ADHD - Kadek Dwipayani; Kertiasih Ni Made; Dyana Paramitha Made Nikita; Gede Agung Anak Agung; Anzelina Dewi (Mimbar Pendidikan Indonesia, 2025)
The learning process not only requires cognitive abilities, but also involves the ability to focus individual attention or concentration on the subject matter. However, not all individuals have the ability to concentrate optimally in the learning process. A child's weak ability to concentrate in learning is generally experienced by children with special needs such as children with Attention Deficit Hyperactivity Disorder (ADHD). Innovative learning models and media are needed that can increase learning concentration in children with ADHD. This research aims to determine learning concentration in ADHD children by using a jigsaw type cooperative learning model assisted by puzzle media. The techniques used in collecting this data, using observation sheets, interviews with teachers, interviews with school principals, conducting assessments of student learning concentration are carried out by collecting data through recording the duration of student concentration during the learning process, as well as documentation used to collect data related to concentration of learning for students with ADHD. Based on data from observations of ADHD children who were treated with the jigsaw cooperative learning model and puzzle media, they achieved a score of 13, this score has decreased compared to the previous score. This shows an increase in the learning concentration of ADHD children in the learning process. Thus, it can be concluded that there is an influence of implementing the jigsaw type cooperative learning model assisted by puzzle media to increase learning concentration in ADHD children.